No evidence for theta power as a marker of hypnotic state in highly hypnotizable subjects - Hiltunen Seppo; Karevaara Maria; Virta Maarit; Makkonen Tommi; Kallio Sakari; Paavilainen Petri (ELSEVIER SCI LTD, 2022)
EEG spectral-power density was analyzed in a group of nine highly hypnotizable subjects via ten frontal, central, parietal, and occipital electrodes under four conditions: 1) wake state, 2) neutral hypnosis, 3) hypnotic suggestion for altering perception of tones, and 4) post-hypnosis. Results indicate no theta-power changes between conditions, challenging previous findings that increased theta power is a marker of hypnosis. A decrease in gamma power under hypnotic suggestion and an almost significant decrease under neutral hypnosis were observed, compared to post-hypnosis. Anteroposterior power distribution remained stable over all conditions. The results are discussed and compared to earlier studies, which report heterogenous findings.